Lingkungan Kerja Fisik, Hubungan Kerja, Dan Tingkat Kesejahteraan Pengaruhnya Terhadap Kinerja Karyawan PT. Taman Burung Citra Bali International Di Singapadu, Gianyar - Bawa, Ida Bagus Agra; Sintaasih, Desak Ketut (E-Jurnal Manajemen, 2014)
The study was conducted at PT. Citra Bali Bird Park International in Singapadu, Gianyar. A number of 100 respondents was selected as the study sample through random sampling method. The results of multiple linear regression analysis showed that the physical work environment, labor relations, to positively influence the level of welfare. Welfare level variables declared dominant influence on the performance of employees of PT. Citra Bali Bird Park International in Singapadu, Gianyar. The company is expected to pay attention to the welfare of employees if necessary to spend more in order to increase the level of employee benefits during the time felt inadequate and can not meet the needs of employees both in terms of salary and allowances. Keywords : work environment, labor relations, welfare, employee performance